Role of Transdermal Drug Delivery System - Alam, Aftab; Machale, Manjunath U; Yadav, Rajkumar Prasad; Sharma, Mukesh; Patel, Akshay Kumar (Asian Journal of Pharmaceutical Research and Development, 2021)
For several decades, many drug types, including tablets, capsules, pills, creams, ointments, liquids, injectables, have been used for the treatment of disease. These dosage forms must be taken multiple times a day to maintain the concentration of the medication. Transdermal drug delivery systems (TDDS), also known as “patches,” are dosage forms Built to deliver a therapeutically efficient quantity of medicine through the skin of a patient. By increasing patient compliance and preventing first pass metabolism, transdermal delivery offers a leading edge over injectables and oral routes. Transdermal drug delivery provides the patient with controlled release of the drug, allowing for a stable blood level profile, leading to decreased systemic side effects and often increased effectiveness over other types of dosage. The primary objective of the transdermal drug delivery system is to deliver drugs with minimal inter-and intrapatient variations into systemic circulation via the skin at a fixed rate.To address the difficulties of drug distribution, primarily oral routes, the transdermal drug delivery system was implemented. Modifications of the materials used were mainly limited to refinements. The present review paper discusses the overall research on the transdermal drug delivery system (TDDS) leading to the current drug delivery system (NDDS). We used convectional dosage method earlier, but we are now using a novel system of drug delivery. The transdermal patch is one of the biggest advances in the delivery of new medicines. The value of the transdermal drug delivery system is that it is a painless drug administration procedure. There are variables that influence the bioavailability of transdermal products. Such as physiochemical and biological factors. Iontophoresis, phonophoresis, electroporation and micro needles, etc, are many new techniques that have drawn interest due to technological development.